(untitled) (REMUNOM, 2025)
The present study deals with the contribution of the fairy tale genre to the teaching-learning process of children with Autism Spectrum Disorder in Early Childhood Education, seeking to investigate how teachers can significantly insert these texts into their pedagogical practice. The work was carried out through field research. Two children with ASD, aged 3 and 4, participated in the research, the teachers leading the classes in which these students were enrolled, in addition to the researcher herself. With the children, data collection took place in three storytelling sessions and semi-structured interviews were carried out with the educators. The results demonstrate that Fairy Tales provide students with the possibility of relating fictional scenes to concrete reality, providing complete development of that individual. That said, it appears that greater appreciation of this literary genre is necessary for children on the autism spectrum.